Large-area and adaptable electrospun silicon-based thermoelectric nanomaterials with high energy conversion efficiencies. Issue 1 (December 2018) - Morata, Alex; Pacios, Mercè; Gadea, Gerard; Flox, Cristina; Cadavid, Doris; Cabot, Andreu; Tarancón, Albert
Abstract Large amounts of waste heat generated in our fossil-fuel based economy can be converted into useful electric power by using thermoelectric generators. However, the low-efficiency, scarcity, high-cost and poor production scalability of conventional thermoelectric materials are hindering their mass deployment. Nanoengineering has proven to be an excellent approach for enhancing thermoelectric properties of abundant and cheap materials such as silicon. Nevertheless, the implementation of these nanostructures is still a major challenge especially for covering the large areas required for massive waste heat recovery. Here we present a family of nano-enabled materials in the form of large-area paper-like fabrics made of nanotubes as a cost-effective and scalable solution for thermoelectric generation. A case study of a fabric of p-type silicon nanotubes was developed showing a five-fold improvement of the thermoelectric figure of merit. Outstanding power densities above 100 W/m2 at 700 °C are therefore demonstrated opening a market for waste heat recovery. To realize waste heat recovery solutions based on thermoelectricity, high-performance materials with device and manufacturing compatibility are required. Here, the authors demonstrate large-area paper-like nanostructured fabrics consisting of aligned nanotubes with high thermoelectric performance.